2006
DOI: 10.1007/s11104-006-9030-6
|View full text |Cite
|
Sign up to set email alerts
|

Using Soil Water Depletion to Measure Spatial Distribution of Root Activity in Oil Palm (Elaeis guineensis Jacq.) Plantations

Abstract: Knowledge of where roots are active is crucial for efficient management of nutrients in tree crops but measurement of root activity is problematic. Measurement using soil water depletion is an approach that has not been tested in a humid climate. We hypothesised that the three dimensional distribution of root activity of a tree crop in the humid tropics (a) can be determined by measuring soil water depletion during rain-free periods, and (b) is influenced by environment (soil type and climate) and surface mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 21 publications
2
37
0
1
Order By: Relevance
“…We found no relationship between root density and SRt. According to Nelson et al (2006) and Wang et al (2008) root density does not accurately reflect root respiration and exudation activities since old coarse roots are usually less active than young fine roots. In addition regression between root density and SRt in Indonesian oil palm plantations on peat performed poorly (0.003 \ R 2 \ 0.29) (Dariah et al 2014) suggesting a weak contribution of root density to spatial variation of SRt.…”
Section: Spatial Trends Temporal Patterns and Biochemical Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no relationship between root density and SRt. According to Nelson et al (2006) and Wang et al (2008) root density does not accurately reflect root respiration and exudation activities since old coarse roots are usually less active than young fine roots. In addition regression between root density and SRt in Indonesian oil palm plantations on peat performed poorly (0.003 \ R 2 \ 0.29) (Dariah et al 2014) suggesting a weak contribution of root density to spatial variation of SRt.…”
Section: Spatial Trends Temporal Patterns and Biochemical Controlsmentioning
confidence: 99%
“…The water table level response of SRt in the forest was very similar to that measured in a Sumatran peat swamp forest (Comeau et al 2013) but much different from the results by Hirano et al (2009) that indicate no change in SRt when the WT was below-ground and a sharp decrease when the WT raised above-ground. In the OP plantations, SRt was linked to the WT level only at the FT position, where root water uptakes are the lowest (Nelson et al 2006). Other studies conducted in OP plantations on peat did not find a control of WT level over SRt.…”
Section: Spatial Trends Temporal Patterns and Biochemical Controlsmentioning
confidence: 99%
“…Dufrêne and Saugier (1993), in a study in the Ivory Coast, confirmed the sensitivity of stomatal conductance to changes in VPD and reported an exponential decline over a range of 0.8 to 2.0 kPa. Nelson et al (2006) observed mean variations by 1.1 kPa in VPD, reaching 1.8 kPa during the day, in evaluations carried out at different sites in Papua New Guinea. When the spatial distribution of rainfall is analyzed, annual rainfall levels of 1,600 to 2,000 mm (Fig 5) can be observed.…”
Section: Resultsmentioning
confidence: 79%
“…In Kedah, Malaysia, Henson and Harun (2007) found that actual evapotranspiration (ET) rates in plants between seven and eight years old during different drought periods ranged between 3.9 and 2.7 mm d -1 and the corresponding ET/ETo (potential evapotranspiration) ratios ranged from 0.85 to 0.50, i.e., the crop's water requirements cannot exceed 50% of the water available in the soil. Nelson et al (2006), in studies carried out at two different sites in Papua New Guinea with annual rainfall between 3,614 mm and 2,415 mm, reported ET for the crop of 3.2 mm d -1 and 4.1 mm d -1 , respectively. Since 1 ha can host 143 oil palms, minimally meeting this water demand of 2.7 mm d -1 would require 27 m 3 with a water demand per plant of 188.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the root zone, roots were measured down to 3-5 m depth (Jourdan and Rey 1997;Schroth et al 2000;Sommer et al 2000). But most of the root biomass and root activity is found in the top 1 m (Ng et al 2003;Corley and Tinker 2003), with for instance 75 % of root activity estimated at 0.8 m depth in Papua New Guinea (Nelson et al 2006) and 0.22 m in Malaysia (Lehmann 2003using data from IAEA 1975.…”
Section: System Boundaries and Accounted Fluxesmentioning
confidence: 99%